The tree and shrub collections of the Polar-Alpine Botanical Garden-Institute - Goncharova, Oxana; Lipponen, Irina; Poloskova, Elena; Zotova, Olesya (Sibbaldia: the International Journal of Botanic Garden Horticulture, 2021)
Polar-Alpine Botanical Garden-Institute (PABGI) is the northernmost in Russia (67о38’N.) and one of the few botanical gardens in the world inside the Arctic Circle. It has a unique collection of live plants, extensive herbarium funds. The article contains a list of the introduced woody plants in the PABSI collection fund. In 2018, the collection funds of woody plants included 27 families, 57 genera, 271 species, 21 subspecies, 14 species, 17 forms, 22 varieties and 22 hybrids. For the overwhelming majority of tree species introduced in PABGI, the presence of flowering / pollination and fruiting / seed production phases of different regularity is characteristic. The collection has 2 species included in the Russian Federation Red List. In the regional Red Lists of Russia there are 232 samples of 78 taxa of woody plants introduced in the PABGI. According to the list of rare species of IUCN, 298 samples of 106 taxa of woody plants have one particular international protection category or another.